Dental caries, gingival health, and oral hygiene of long term survivors of paediatric malignant diseases. Issue 2 (February 1995) - Dens, F; Boute, P; Otten, J; Vinckier, F; Declerck, D
Abstract : Fifty two children who had had cancer and been treated with chemotherapy, and who were long term event free, were examined for caries prevalence, gingival health, and oral hygiene and compared with a control group. A higher dental caries prevalence for the 14-17 year age group was noted. The restorative index was significantly lower in the age group 10-13. There were no significant differences in gingival index, plaque index, or toothbrushing frequency. It is concluded that these patients should be considered as at high risk for caries after cancer treatment. Professional dental follow up should be integrated in the medical follow up.